Are the Evenki reindeer herders still nomads? The alternate use of different types of spaces in Inner Mongolia, China - Dumont, Aurore (Études mongoles et sibériennes, centrasiatiques et tibétaines, 2018)
The last six decades of Chinese state policies has led to the transformation of the Evenki reindeer herders’ domestic economy, a more systematic use of fixed homes and the reduction of the grazing areas. Paradoxically, the herders’ mobility has become more flexible and extensive, while herding skills remain a fundamental component of their way of life. The present paper explores the contemporary nomadic practices of the Evenki by examining their annual moves between village and camp. The constant movement of the herders between these two complementary spaces reflects their strategies for adapting to ecological and political challenges. Les politiques étatiques chinoises de ces six dernières décennies ont conduit à la transformation de l’économie domestique des Évenks éleveurs de renne, à une utilisation accrue d’habitats fixes, et à la réduction des zones de pâturage. Paradoxalement, la mobilité des éleveurs est devenue plus flexible et étendue, tandis que les compétences liées à l’élevage demeurent une composante fondamentale de leur mode de vie. Le présent article étudie les pratiques nomades contemporaines des Évenks en examinant leurs mouvements annuels entre village et campement. Les mouvements constants des Évenks entre ces deux espaces complémentaires reflètent leurs stratégies d’adaptation aux défis écologiques et politiques.